Pengaruh Infrastruktur, Potensi Pasar Mice, dan Dukungan Kebijakan Terhadap Penyelenggaraan Mice Berbasis Lingkungan Melalui Keberhasilan Penyelenggaraan - Edwin Edwin; Rahmat Ingkadijaya; Agus Riyadi; Myrza Rahmanita (Jurnal Ilmiah Pariwisata, 2026)
This study aims to analyze the effect of infrastructure, MICE market potential, and policy support on environmentally based MICE implementation through the mediation of event success at Kebun Raya Bogor as a conservation-based destination. The research adopts a quantitative approach with an explanatory research design. Data were collected from 120 respondents involved in the MICE industry in West Java using a Likert-scale questionnaire and analyzed using SmartPLS 4. The results indicate that infrastructure, MICE market potential, and policy support have a positive and significant effect on both event success and environmentally based MICE implementation. Event success is also found to significantly influence green MICE implementation and mediates the relationship between the independent variables and the dependent variable. Among the predictors, policy support emerges as the most dominant factor influencing event success. Event success is identified as a key mechanism in driving the implementation of green MICE in conservation-based destinations. Therefore, strengthening green infrastructure, enhancing sustainability-oriented market potential, and integrating comprehensive policy support are essential factors for developing sustainable MICE destinations. Keywords: Infrastructure, MICE market potential, Policy support, event success, Environmentally sustainable